PERANCANGAN APLIKASI TRACER STUDY ALUMNI JURUSAN ADMINISTRASI BISNIS POLITEKNIK NEGERI BANJARMASIN BERBASIS WEB - Tajudin Noor; Said Muhamad; Rahma Indera (P3M Politeknik Negeri Banjarmasin, 2016)
Graduates is one of the important components within an educational institution in addition to students, faculty and stakeholders. Graduates is an educational product used by public. So it can be said that the Graduates is one of the parameters to determine the success or failure of educational instituusi.To find the career increment and Graduate’s life, Business Administration Program Study State Polytechnics of Banjarmasin have a unit. Some way to gathering information about graduates with the phone and fill in form directly by graduates. Based on existing mechanisms, still have some weaknesses, they are not all of graduates are willing to be contacted by the officers, and not all graduates can fill in a form.The purpose of this application is facilitate the collect of information on the graduates website for the application form so that most of graduates can access it more easily. This application was made with Waterfall development method.